From the Written Word to the Egocentric Network: Applying Network Analysis to the Epistolary Exchanges of Karl von Lichtenstein-Castelcorno, Prince-Bishop of Olomouc, with the Roman Curia in the Late Seventeenth Century (1666–1695) - Marangon, Elisa (Umanistica Digitale, 2025)
In recent years, numerous disciplines in the field of humanities have expanded their research perspectives by adopting a critical interdisciplinary approach to studying Early modern sources, often incorporating the use of digital technologies. This approach aims to analyze the possibilities and limitations of sources in a complex and integrated manner, acknowledging their inherent partiality and fragmentation. This contribution aligns with this line of research and seeks to investigate, through historical and quantitative analysis, the correspondence of the prince-bishop of Olomouc Karl von Lichtenstein-Castelcorno (1624-1695, bishop from 1664) with his most influential correspondents at the Holy See during the last three decades of the seventeenth century (1666-1695). By creating datasets and graphs using the statistical software R and employing the methodology of egocentric network analysis, the study seeks to identify the most enduring connections within the bishop’s correspondence, highlighting both the types of communications and the composition of his epistolary network. Furthermore, it examines the relationships with cardinals, popes, and prominent secretaries of the Roman Curia during his thirty-year lasting episcopate in Olomouc.